Knowledge, Attitudes, Challenges and Coping Strategies Amongst Caregivers of Children with Cerebral Palsy in Dar Es Salaam, Tanzania (Tanzania Medical Journal, 2020)
BackgroundCerebral palsy (CP) is a disorder in the development of posture and movement causing activity limitation due to a non-progressive injury on the developing fetal or infant brain. Advanced medical care has increased the survival of children with CP, resulting in an increased burden of care for caregivers. The continuum of care for a child with CP depends on the caregivers’ understanding of their condition, complications and required treatment. Therefore, an understanding of the knowledge gaps, attitudes, challenges and coping strategies amongst caregivers raising children with CP, will help clinicians to develop more family-oriented treatment protocols incorporating caregivers’ needs.ObjectivesWe aimed to determine the level of knowledge, attitudes, challenges and coping strategies amongst caregivers raising children with cerebral palsy at Muhimbili National Hospital.MethodA cross-sectional, hospital-based study using structured interviews was conducted amongst 139 consecutively recruited caregivers. A pre-tested questionnaire was used to collect information including: social demographics, caregivers’ attitudes towards CP and challenges involved in caring for children with CP. Univariate analysis was done and summarized using frequencies; Fischer’s exact test was used to determine association between factors influencing caregiver’s knowledge and attitudes.ResultsOf the 139 caregivers, only 20.9% showed satisfactory knowledge on CP. Persistent negative attitudes amongst caregivers were significantly influenced by the severity of CP (p?0.001), caregivers’ level of knowledge on CP (p?0.001), their satisfaction with the diagnosis disclosure process (p=0.031), the perceived negative attitudes of their partners (p=0.006), extended families (p=0.001) and the society (p=0.010). Challenges facing caregivers of children with CP included: an increased burden of care, broken family relationships and increased expenditure. Caregivers coped by quitting work and up to 64.7% sought spiritual and/or traditional healing, which showed limited understanding of CP.Conclusion and RecommendationsCaregivers’ level of knowledge on CP was low, which can be improved by comprehensive disclosure of the CP diagnosis by healthcare personnel through stage-wise counseling. Family support is key in helping caregivers’ improve their attitudes and cope with the major challenges facing them. Policy makers should ensure the decentralization of comprehensive CP clinic services to ensure access to rehabilitative health care, including the provision of health education and caregiver support from the health system to the community level. Keywords: Cerebral Palsy, Knowledge, Attitudes, Challenges, Coping.